Epidemiology and new opportunities of investigating risk factors for congenital malformations in Northwest Russia: a registry-based linkage study - Kovalenko, Anton Alexandrovich (International Journal of Environmental Research and Public Health, 2018)
Birth defects constitute an important public health issue as they are the main causes of perinatal and infant mortality. To address incomplete data coverage in Russia, the studies described in this thesis all have a registry-based study design, and were based on the linkage of the Murmansk County Birth Registry (MCBR) and the Murmansk Regional Congenital Defects Registry (MRCDR) to investigate the epidemiology and selected risk factors for congenital malformations. The study population included all 52 806 births recorded in the MCBR during 2006-2011 and were followed up to two years after birth through MRCDR. Chi-squared tests were applied to evaluate differences in distribution of selected risk factors. Logistic regression was used to estimate the effect of risk factors on the occurrence of some defects. Routine under-reporting of major birth defects to the MRCDR of 40% cases occurred in Murmansk County. Hypospadias was the most common birth defect with a prevalence of 25.7 per 10 000 newborns and the cases were associated with cervical erosion, low infant birthweight and preeclampsia. Smoking, alcohol abuse during pregnancy and maternal diabetes mellitus were also risk factors for delivering infants with ventricular septal defects. Potentially numerous cases of hypospadias and ventricular septal defects are preventable in Russia if health policy makers were to give more attention to established risks. Public health efforts should therefore focus on reducing smoking and alcohol consumption, as well as improving diabetes control in pregnant women.